2019
DOI: 10.1088/1742-6596/1294/5/052067
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric determination of Amoxicillin using 4-Aminoantipyrine and the effects of different parameters

Abstract: The wide utilize of antibiotics has led to spreading of antibiotics resistance among bacterial populations and reducing the effectiveness of antibiotics. However, most of the administrated antibiotics enter the environmental matrixes through direct runoff and excretion of feces or urine as unchanged original drugs, active metabolites and/or degradation products. Amoxicillin is one of the most valuable and highly consumed antibiotics. Thus, amoxicillin removal from pharmaceutical wastes offers many economic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The volume of NaNO 2 salt has an effective part in this reaction so it has been studied and determined the best volume, which leads to a fast and higher absorbance.The data indicated that the better volume of Sodium nitrite salt 3 mL for dopamine and adrenaline as appear in Figure 4.The better time for the reaction complete and the formation of the diazonium salt was about 5 minutes, several periods of time were studied among 2-60 minutes 12,13,17,18 as appeared in Figure 5.…”
Section: Influence Of Volume Of Nano 2 Salt and Timementioning
confidence: 93%
“…The volume of NaNO 2 salt has an effective part in this reaction so it has been studied and determined the best volume, which leads to a fast and higher absorbance.The data indicated that the better volume of Sodium nitrite salt 3 mL for dopamine and adrenaline as appear in Figure 4.The better time for the reaction complete and the formation of the diazonium salt was about 5 minutes, several periods of time were studied among 2-60 minutes 12,13,17,18 as appeared in Figure 5.…”
Section: Influence Of Volume Of Nano 2 Salt and Timementioning
confidence: 93%
“…The best absorption value of the chromium complex was within the temperature range of 10-30, where it reached its peak and gave the best color intensity. At higher temperatures, the absorbance decreased, possibly due to a decrease in stability or dissociation of the complex at high temperatures [31][32][33] as shown in Figure 7.…”
Section: Effect Of the Temperaturementioning
confidence: 97%
“…The study examined the effectiveness of Cu, N@CQDs when used with AMX, along with 4-NH 2 -APE and aqueous H 2 O 2 solution. In previous studies, the compound 4-NH 2 -APE has been employed to quantify AMX [ 77 ]. The highly colored pink quinoneimine product was obtained through the oxidative coupling of AMX and 4-NH 2 -APE in an alkaline medium (pH 10.0) with H 2 O 2 .…”
Section: Applications Of Mixed-doped Cqdsmentioning
confidence: 99%
“…The observed decrease in fluorescence intensity of Cu, N@CQDs can be explained by the overlap between the absorption band of the resulting chromogen at 505 nm. The quenching phenomenon suggested the result of the inner-filter effect (IFE) [ 77 , 78 ]. Moreover, the observed fluorescence quenching of Cu, N@CQDs can be ascribed to quenching mechanisms.…”
Section: Applications Of Mixed-doped Cqdsmentioning
confidence: 99%